2020
DOI: 10.1080/17543266.2020.1762249
|View full text |Cite
|
Sign up to set email alerts
|

Soft manikin as tool to evaluate bra features and pressure

Abstract: Soft manikin as tool to evaluate bra features and pressureAccurate evaluations of the interface pressure between the bra and skin are critically important prerequisites for the ergonomic design of bra components.Nevertheless, previous analyses on contact pressure have mainly relied on human wear trials with low data repeatability. Determining suitable pressure and tension of shoulder strap and underband to provide adequate breast support has been largely empirical. In this study, a manikin with breast prosthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Comfortable clothing pressure is normally under 4.00 kPa; the comfort pressure ranges of different parts of the sports bras are as follows: the shoulder point is 1.61-2.14 kPa, the chest area is 2.01-4.47 kPa and the underband area is 1.69-2.74 kPa. [26][27][28] Pressure values for all test points except point B are in the comfortable range. The pressure at point B exceeds the comfort range, possibly due to the hardness of the mannequin material compared to the human body, resulting in an overall high pressure value.…”
Section: Sports Bra Pressurementioning
confidence: 87%
“…Comfortable clothing pressure is normally under 4.00 kPa; the comfort pressure ranges of different parts of the sports bras are as follows: the shoulder point is 1.61-2.14 kPa, the chest area is 2.01-4.47 kPa and the underband area is 1.69-2.74 kPa. [26][27][28] Pressure values for all test points except point B are in the comfortable range. The pressure at point B exceeds the comfort range, possibly due to the hardness of the mannequin material compared to the human body, resulting in an overall high pressure value.…”
Section: Sports Bra Pressurementioning
confidence: 87%
“…The participants were required to run for 15 min on a treadmill at 8 km/h in each bra condition. The Novel Pliance-X pressure system, which has been validated for measuring the interfacial pressure induced by garments onto the human body, was used to measure the bra-skin pressure by placing the sensor between the skin and the bra components [ 24 , 25 ]. The strip sensor used was 10 mm in diameter (in a contact area of 78.54 mm 2 ) and 0.95 mm in thickness.…”
Section: Methodsmentioning
confidence: 99%
“…Contact pressure and comfort are two distinct aspects in which the performance of brassiere straps is evaluated. 6 Prior studies in which they analyzed brassiere strap pressure and discomfort, reported no significant pressure difference recorded between cross-back and vertical brassiere straps with or without cushion pads. Bowles and Steele 7 concluded that discomfort of the brassiere straps can't be eliminated by varying orientation of straps, and that study also has many limitations.…”
Section: Introductionmentioning
confidence: 97%
“…Contact pressure and comfort are two distinct aspects in which the performance of brassiere straps is evaluated. 6…”
Section: Introductionmentioning
confidence: 99%